Mengembangkan Kecerdasan Spiritual Anak Melalui Pendidikan Agama - Yuliatun, Yuliatun (PIAUD Universitas Islam Negeri Sunan Kudus, 2013)
Naturally, Every child born has brought potential for good, that willfoster a sense of potential and needs to know and close to Allah who created him.Communication that is built will bring up commendable attitudes and alwaysincline to virtue. This is the characteristics of spiritual potential that contain highvalues of humanity. The values will be wise and make coverage always attenddeep meaning and value in their actions. Religious education can be used as amedium or tool to a activate children spiritual intelligence potency in addition totheir emotional and intelectual ones. This paper analyzes how the importance ofreligious education which is reinforced by the meaning of each Islamic dimension(faith, Islam, and ihsan) in every facet of human life.